Personality and Proficiency: Investigating How Extrovert-Introvert Traits Relate to English Speaking Performance - Korah, Fernoldion Juliano France; Sengkey, Virginia Gabrella (FOSTER: Journal of English Language Teaching, 2025)
This study examines the correlation between extrovert-introvert personality types and speaking performance among tenth-grade students at a private high school in Manado, North Sulawesi during the 2024/2025 academic year. Using a quantitative approach, this research employed both correlational and comparative designs to explore whether personality traits impact speaking performance. A sample of 104 students completed the Eysenck Personality Questionnaire (EPQ), categorizing them into extrovert, introvert, and ambivert groups. Speaking performance was measured through mid-test scores in English-speaking class. The results indicate no significant correlation between personality type (extrovert and introvert) and speaking performance, with Pearson correlation coefficients of 0.232 (extrovert) and 0.231 (introvert) showing weak, non-significant relationships. However, comparative analysis via t-tests revealed a significant difference in performance between personality types, with introverted students achieving higher mean scores (M = 86.93, SD = 10.13) than extroverted students (M = 81.73, SD = 14.32), suggesting greater performance consistency among introverts.